Justification and implications of the introduction of an expanded Close Marking System for the Fellowship Examination. Issue 6 (30th April 2013) - Beasley, Spencer W.; Wannan, Cassandra; Hardware, Narelle
Abstract Critical review of the close marking system used in the Fellowship Examination revealed that minor modifications to the way in which it was employed could significantly improve the quality (reliability and validity) of the examination. In addition, it could provide better information for the specialty courts to use during their discussion of the borderline candidate at their mini‐court meetings. An expanded close marking system (ECMS) probably has little impact on the overall pass rate, but it does improve the ability to determine the marginal candidate. In addition, it has the capacity to provide feedback on examiner performance and provides the specialty courts with a tool to assess the quality of their questions. Analysis of data collected during several 'live trials' of ECMS has shown that the implementation of the ECMS represents a further improvement in the processes around the Fellowship Examination.